A laboratory technique of fungicide evaluation against Allbugo candida causing white rust of Brassica juncea - and G.D. MUNSHI, S.S. SOKHI*, R.K. GREWAL (Indian Phytopathology, 2002)
An in vitro technique for the evaluation of fungicides against A. candida infecting Indian mustard is described.